MANAJEMEN STRATEGI DALAM MENINGKATKAN KUALITAS PELAYANAN UMRAH DI PT AR-RAHMAH WISATA - Kahfi, Al (Yonetim Jurnal, 2024)
This study discusses "Strategic Management in Improving the Quality of Umrah Services at PT. Ar-Rahmah Wisata" which is the background of this research is firstly the lack of human resources at PT Ar-Rahmah Wisata, secondly the lack of facilities available at PT Ar-Rahmah Wisata, and thirdly in the administrative process of prospective pilgrims there is a lack of synchronization of identity documents pilgrims themselves, thus complicating the process of making passports and other documents. This study aims to determine the management strategy of PT Ar-Rahmah Wisata in improving the quality of Umrah services, then to find out what are the inhibiting factors in improving the quality of Umrah services at PT Ar-Rahmah Wisata. This type of research is a qualitative research, with secondary and primary data sources. With data collection techniques using observation, interviews and documentation. The data analysis technique in this study is descriptive qualitative by means of data reduction, data presentation, and conclusions. The results obtained from this study are for the management strategy carried out by PT Ar-Rahmah Wisata in Improving Service Quality by applying the three stages of the theory put forward by Bambang Hariadi: Formulation of the planned strategy: recruiting good, friendly, and responsive and have skills, provide training to its employees, provide guidance and training to congregations, as well as provide information services and ease of payment, Strategy Implementation, PT Ar-Rahmah Wisata implements it optimally so that it can improve its service performance to the fullest, and Strategy Evaluation results of PT. Ar-Rahmah Wisata looks successful and effective, the evaluation is done by Measuring Employee Performance and re-evaluating the implementation of the previous strategy.